2015
DOI: 10.1016/j.jmaa.2015.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Optimal extensions of the Banach–Stone theorem

Abstract: Let C 0 (K, X) denote the Banach space of all X-valued continuous functions defined on the locally compact Hausdorff space K which vanish at infinity, provided with the supremum norm. We prove that if X is a real Banach space and T is an isomorphismwhere J(X) is the James constant of X, then K 1 is homeomorphic to K 2 . In the complex case, we provide a similar result for reflexive spaces X. In other words, we obtain a vector-valued extension of the classical Amir-Cambern theorem (X = R or X = C) which at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…It is worth mentioning that in [14,Section 6], there is given a similar description of the second dual space of C 0 (K, E), where K is just locally compact. We will need to use only the case when K is compact, though.…”
Section: Notation and Auxiliary Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth mentioning that in [14,Section 6], there is given a similar description of the second dual space of C 0 (K, E), where K is just locally compact. We will need to use only the case when K is compact, though.…”
Section: Notation and Auxiliary Resultsmentioning
confidence: 99%
“…Many of those results were recently unified and strengthened in [14], where it was showed that if E is a real or complex reflexive Banach space with λ(E) > 1, then for all locally compact spaces K 1 , K 2 , the existence of an isomorphism T : C 0 (K 1 , E) → C 0 (K 2 , E) with T · T −1 < λ(E) implies that the spaces K 1 , K 2 are homeomorphic. Here λ(E) = inf{max{ e 1 + λe 2 : λ ∈ F, |λ| = 1} : e 1 , e 2 ∈ S E } is a parameter introduced by Jarosz in [29].…”
Section: 2])mentioning
confidence: 94%
See 3 more Smart Citations